2016
DOI: 10.1167/iovs.15-18158
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Serum Levels of Testosterone and Estradiol With Meibomian Gland Assessments in Postmenopausal Women

Abstract: PurposeThe aims of this analysis were to determine if there is an association between serum levels of testosterone and estradiol with meibomian gland (MG) morphology and lipid layer thickness.MethodsThe data used for this analysis were collected from postmenopausal women with and without dry eye disease. Meibography was used to assess MG dropout on the central two-thirds of the eyelid and biomicroscopy was used for assessing MG expressibility and meibum quality. Venous blood samples were drawn for serum hormon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 47 publications
1
21
0
1
Order By: Relevance
“…In a separate study, venous blood sampling and meibography were used to evaluate the association between serum levels of testosterone and estradiol and MG morphology in postmenopausal women ( n = 198, average age 61.2 [±9.1] years). 52 MG dropout increased with higher testosterone levels, and a significant difference in testosterone levels was observed in the mild versus severe MG dropout groups (MG dropout scores of 1 and 4, respectively; p = 0.002). Differences were not significant with estradiol and meibography assessments ( p = 0.53).…”
Section: Biological Sex and Hormonal Differences In Ocular Structurementioning
confidence: 90%
“…In a separate study, venous blood sampling and meibography were used to evaluate the association between serum levels of testosterone and estradiol and MG morphology in postmenopausal women ( n = 198, average age 61.2 [±9.1] years). 52 MG dropout increased with higher testosterone levels, and a significant difference in testosterone levels was observed in the mild versus severe MG dropout groups (MG dropout scores of 1 and 4, respectively; p = 0.002). Differences were not significant with estradiol and meibography assessments ( p = 0.53).…”
Section: Biological Sex and Hormonal Differences In Ocular Structurementioning
confidence: 90%
“…It should be noted that hormonal and environmental influences on the structure of meibomian glands may be confounding factors in such studies, however. 28,29…”
Section: Agingmentioning
confidence: 99%
“…9 This finding was also different to a study conducted by Anna et al where the mean age was 61.2±9.1 years. 11 In this study significant association was found between dry eye disease and increasing age. Similar findings were found in a study conducted in Australia where the odds for developing dry eyes were 1.04 at 95% CL=1.01, 1.06).…”
Section: Discussionmentioning
confidence: 50%